Liquor Store Theatre - Stovall, Maya, 1982- (Black outdoors., 2020)
"For six years, Maya Stovall staged Liquor Store Theatre, a conceptual art and anthropology video project in the streets and sidewalks surrounding the liquor stores in her Detroit neighborhood. In LST, staged and video-recorded performances are the start of conversations with neighbors. On the streets and sidewalks next, neighbors discuss everything from economics, to politics, to aesthetics, to affect, to drugs, sex, work, and daily life. Following a screenplay structure, Stovall moves, one-by-one, through her Liquor Store Theatre (2014-) video series seen in the Whitney Biennial. In the scenes of her LST video reflections, Detroit's McDougall Hunt neighborhood comes alive"--